Pengaruh Kompetensi, Efikasi Diri, Motivasi, Dan Lingkungan Kerja Terhadap Kinerja Pegawai Aparatur Sipil Negara (ASN) Dan Tenaga Harian Lepas (THL) Dinas Perpustakaan Kabupaten Indragiri Hulu - Yuni Pitri; Marzolina Marzolina; Rosnelly Roesdi (CV. Ulil Albab Corp, 2024)
This research aims to determine the influence of competence, self-efficacy, motivation and work environment on the performance of state civil servants (ASN) and casual daily workers (THL) at the Indragiri Hulu Regency Library Service located on Jalan Regent Tulus, Sekip Hulu, Kec. Rengat, Indragiri Hulu Regency, Riau 29319. This research is quantitative research with data collection using interview methods and distributing questionnaires. The research population and sample were 77 employees consisting of 32 ASN people and 45 THL people. The sampling technique uses a saturated sampling technique. The analytical tool in this research is multiple linear regression analysis with the help of the SPSS program. The research results show that Competence, Self-Efficacy, Motivation and Work Environment simultaneously have a positive and significant effect on the performance of ASN and THL employees. Based on the research results, it also shows that Competency, Self-Efficacy, Motivation and Work Environment partially have a significant effect on the performance of ASN and THL employees.